Effect of calcination time on the adsorptive capacity of molybdenum oxides for the removal of methylene blue in aqueous solution - Filho, Jorge Fernandes; Leite Mathias, Samir; Lopes, Henrique Solowej Medeiros; Carriello, Giovanni Miraveti; Barros, Marcus Felippe de Jesus; de Mendonça, Vagner Romito; de Menezes, Aparecido Junior (Disciplinarum Scientia | Naturais e Tecnológicas, 2025)
The increasing industrialization process and the discharge of pollutants into water bodies have been concerns since the beginning of industrialization. To ensure safe access to water, new purification methodologies and stricter regulations are necessary. This study aims to develop materials for the removal of methylene blue (MB) dye in aqueous systems. Materials were synthesized through the oxidation of molybdenum disulfide (MoS₂) and subjected to different calcination times, seeking a balance between energy consumption and adsorption capacity. The elemental composition of the samples was analyzed by Scanning Electron Microscopy with Energy Dispersive X-ray Spectroscopy (SEM-EDS), X-ray Diffraction (XRD), and Fourier-Transform Infrared Spectroscopy (FTIR) revealed the transformation of MoS₂ to molybdenum trioxide (MoO3) proportional to the thermal treatment time. The kinetic analysis of MB adsorption revealed that the sample calcined for 300 minutes exhibited the highest efficiency in dye removal from the solution, with an adsorption capacity of 41.6 mg.g-1 after 300min. This capacity was significantly higher than that of the sample calcined for 30 minutes during the same period of time (18.6 mg.g-1), representing a 124% increase. Compared to the precursor material (6.60 mg.g-1), the improvement in adsorption capacity was even more expressive, with a 530% increase. Tests adsorption isotherms indicated that the maximum adsorption capacity of the sample calcined for 300 minutes was 379.0 mg.g-1. Equilibrium tests indicated that the maximum adsorption capacity of the sample calcined for 300 minutes was 379.0 mg.g-1. The greater dispersion in aqueous media of the calcined sample, compared to the others, is attributed to the presence of molybdenum oxide, favoring the adsorption of the dye onto the surface of the material formed.